KEABSAHAN KONTRAK ELEKTRONIK DALAM TRANSAKSI BISNIS DI TINJAU MENURUT UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Herluin Eka Dharmawan Soesilo (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACT The development of technology, especially the internet, provides many conveniences for human life, one of which is in the field of electronic contracts. However, on the other hand, this progress also brought new problems. Electronic contracts as a form of trade that is currently experiencing rapid development are also inseparable from problems in its implementation. With this type of contract, the need for face-to-face meetings between the parties can be reduced or even eliminated altogether. The absence of physical presence from the parties is very possible to bring problems to the validity of the electronic contract itself in relation to the ability to do legal actions by the parties. This study aims to see whether an electronic contract can be said to be valid and how the power of electronic contracts if a dispute occurs, especially in Indonesia.This study uses an empirical method, to analyze the validity of electronic contracts in the conduct of buying and selling transactions through an electronic system carried out by parties who are not yet old enough. The electronic contract referred to above is theoretically considered invalid, but as long as it does not bring adverse consequences to the opposing party and there is no cancellation, the contract is considered binding for the parties.From the results of the study it was found that there are differences of opinion in terms of the validity of electronic contracts and the strength of proof of electronic contracts as evidence (invalid and cannot be used as evidence), notary public (one notary believes that electronic contracts are invalid and cannot be used as evidence: one notary is of the opinion that an electronic contract can be said to be acceptable as evidence).From this research it can be concluded that there is still uncertainty regarding the validity and strength of contracts conducted electronically as business transactions Keywords: Transactions, Contracts, Electronic Agreements